2015
DOI: 10.5812/ijhrba.20021v2
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Features in Students: the Predicting Role of Schema, Emotion Regulation, Dissociative Experience and Suicidal Ideation

Abstract: Background:Numerous studies have demonstrated that early maladaptive schemas, emotional dysregulation are supposed to be the defining core of borderline personality disorder. Many studies have also found a strong association between the diagnosis of borderline personality and the occurrence of suicide ideation and dissociative symptoms.Objectives:The present study was designed to investigate the relationship between borderline personality features and schema, emotion regulation, dissociative experiences and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
(44 reference statements)
4
10
0
1
Order By: Relevance
“…Akin to other similar studies, the current research showed that BPD patients exhibited relatively high scores in all schema domains, but specifically in disconnection/rejection (Ball & Cecero, 2001;Jovev & Jackson, 2004;Lawrence et al, 2010;Meyer et al, 2001;Nilsson et al, 2010;Sajadi et al, 2015;Specht et al, 2009;Taylor & Reeves, 2007). Our research also found high scores in other-directedness, which were relatively greater when compared with other studies among BPD patients (Cohen et al, 2016;Shorey et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Akin to other similar studies, the current research showed that BPD patients exhibited relatively high scores in all schema domains, but specifically in disconnection/rejection (Ball & Cecero, 2001;Jovev & Jackson, 2004;Lawrence et al, 2010;Meyer et al, 2001;Nilsson et al, 2010;Sajadi et al, 2015;Specht et al, 2009;Taylor & Reeves, 2007). Our research also found high scores in other-directedness, which were relatively greater when compared with other studies among BPD patients (Cohen et al, 2016;Shorey et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Regarding this issue, Young (1999) first proposed that several EMSs were particularly central to BPD, including those related to abandonment, dependence, mistrust, abuse, subjugation, emotional deprivation, and insufficient self-discipline. In addition, several empirical studies have shown sound evidence for the relationship between the intensity of EMSs and BPD severity, in both clinical and nonclinical populations (Ball & Cecero, 2001;Corral & Calvete, 2014;Meyer, Leung, Feary, & Mann, 2001;Sajadi, Arshadi, Zargar, Mehrabizade Honarmand, & Hajjari, 2015;Shorey, Anderson, & Stuart, 2014;Specht, Chapman, & Cellucci, 2009;Taylor & Reeves, 2007). Despite this progress, it remains unclear whether EMSs are directly associated with relevant aspects of dimensional psychopathology in BPD, such as internalizing symptoms, psychotic-like symptoms, suicidal ideation, or aggressiveness, which could provide a more comprehensive framework on the overall influence of EMSs on people with BPD (Black, Blum, Pfohl, & Hale, 2004;Látalová & Prasko, 2010;Lee, Allen, Black, Zanarini, & Schulz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study results also indicated that both emotion regulation strategies of reappraisal and suppression were significant predictors of borderline personality and its components. This finding is in line with the results of Bashrpoor, Toloi Mehmandoost Olya, Narimani, and Atadokht (2014) and Sajadi, Arshadi, Zargar, Mehrabizade Honarmand, and Hajjari (2015). Emotion regulation strategies are an effective way to change emotions, feelings, desires, beliefs, and practices of the individual and giving order and meaning to daily life so that one can reach higher goals; people's success in reaching goals is determined according to their skills in emotion regulation, knowledge, and behavior (Jazaieri, McGonigal, Jinpa, Doty, Gross, & Goldin, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The TSDP model further posits that persistent failure to recognize negative emotions as they occur impairs emotion regulation ability and heightens negative emotionality over time in BPD patients (Troisi et al, 2000;Ford and Courtois, 2014;Mosquera et al, 2014;Sajadi et al, 2015). Our right amygdala finding is likely reflecting this process, as early traumatic stress has been linked to amygdala shrinkage in adulthood possibly due to hypothalamic-pituitaryadrenocortical axis hyper-reactivity (Leichsenring et al, 2011;Pechtel et al, 2014) and low right amygdala GMV has been associated with depression and anxiety (Hayano et al, 2009;van Mierlo et al, 2015).…”
Section: Gmv Differences Associated With Agementioning
confidence: 99%